Induced Neurons From Germ Cells in Caenorhabditis elegans - Marchal, Iris; Tursun, Baris (Frontiers in Neuroscience, 2021)
Cell fate conversion by the forced overexpression of transcription factors (TFs) is a process known as reprogramming. It leads to de-differentiation or trans-differentiation of mature cells, which could then be used for regenerative medicine applications to replenish patients suffering from, e.g. neurodegenerative diseases, with healthy neurons. However, TF-induced reprogramming is often restricted due to cell fate safeguarding mechanisms, which require a better understanding to increase reprogramming efficiency and achieve higher fidelity. The germline of the nematode Caenorhabditis elegans has been a powerful model to investigate the impediments of generating neurons from germ cells by reprogramming. A number of conserved factors have been identified that act as a barrier for TF-induced direct reprogramming of germ cells to neurons. In this review, we will first summarize our current knowledge regarding cell fate safeguarding mechanisms in the germline. Then, we will focus on the molecular mechanisms underlying neuronal induction from germ cells upon TF-mediated reprogramming. We will shortly discuss the specific characteristics that might make germ cells especially fit to change cellular fate and become neurons. For future perspectives, we will look at the potential of C. elegans research in advancing our knowledge of the mechanisms that regulate cellular identity, and what implications this has for therapeutic approaches such as regenerative medicine.